Wearable with integrated piezoelectric energy harvester for geolocation of people with Alzheimer's - Linder Rubiños Jimenez, Santiago; Herber Grados Gamarra, Juan; Nelson Chávez Gallegos, Eduardo; Angélica Velasquez Jimenez, Linett; Junior Grados Espinoza, Herbert; Christian Pesantes Arriola, Genaro (Institute of Advanced Engineering and Science, 2024)
Alzheimer's is a progressive disease that affects memory, causing disorientation in the patient, which causes them to lose themselves, generating anguish in families who have to resort to expensive searches. The objective of this research was to implement a device that can remotely provide the location of the Alzheimer's patient over a long period to relatives for greater security. For this, in this research, a mobile application was developed that receives information from a wearable that applies the internet of things using ong-range wide area technology to show the patient's real-time location and uses piezoelectrics for greater battery autonomy. The real-time location of the person and the radius of the safe zone in the application were obtained as results, the received signal strength indicator value where the signal was excellent or good had a value of -30 to -89 dB between 0 to 400 meters and the battery discharge time was 11 hours and 44 minutes. It was concluded that the application is interactive, that the piezoelectric system increased the autonomy of the wearable, and that the long-range wide area (LoRa) technology allowed monitoring of the patient's location with great precision at 400 meters.